Resiliency Scale (RS): Scale Development, Reliability and Validity Study - Uğur GÜRGAN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The purpose of this study was to develop a new Resiliency Scale (RS) for Turkish samples. Various items from some major resiliency scales, most of them with some partial change, were collected and a pool of 228 items containing almost all possible resilience areas were obtained. This item-pool was administered to a college sample of 419. Resulting of analysis 50 item RS were obtained and administered to a new college sample of 112 participants. This second sample has also received the Rosenbaum’s Learned Resourcefulness Hopelessness Scale and Problem Solving Inventory. Results, Pearson Locus